(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This thesis systematizes, based on an analysis of scientific sources, the key agronomic factors that ensure stable yield and high fruit quality in raspberry (Rubus idaeus L.) plantations. In particular, it briefly addresses site selection and agroecological soil assessment (soil fertility, pH, and water holding capacity), plant nutrition and water supply (fertilizer application rates and irrigation scheduling), plantation management technologies (support/trellis systems, pruning, and training), as well as the effects of integrated pest and disease management (IPM) approaches on plantation performance. Practical recommendations aimed at improving resource-use efficiency and enhancing phytosanitary sustainability are summarized. It is emphasized that raspberry yield and fruit quality largely depend on site conditions, planting technologies, and irrigation regimes. The factors discussed are crucial for ensuring fruit quality, productivity, and environmental sustainability.